The Impact of a Professional Development Program on English Language Teachers' Classroom Performance - Frank Giraldo (Universidad Nacional de Colombia, 2014)
This article reports the findings of an action research study on a professional development program and its impact on the classroom performance of in-service English teachers who worked at a language institute of a Colombian state university. Questionnaires, semi-structured interviews, class observations, and a researcher's journal were used as data collection instruments. Findings suggest that these in-service teachers improved their classroom performance as their teaching became more communicative, organized, attentive to students' needs, and principled. In addition, theory, practice, reflection, and the role of the tutor combined effectively to help the in-service teachers improve classroom performance. It was concluded that these programs must be based on teachers' philosophies and needs and effectively articulate theory, practice, experience, and reflection.